Hello Jamal, Given:   Width (W) = 8 inches              Perimeter (P) = 42 inches What to find : Length Formula for perimeter of rectangle is P = 2L + 2W Plug in the values of P and W in the formula...

Hello Char, The domain is all the x-values, and the range is all the y-values. a) f(x) = 4x2 - 7x +3 This is a polynomial. There are no denominators (so no division-by-zero) and no radicals (so no square-root-of-a-negative). There are no values that you can't plug in for x. When...

Emily, Step 1. Get rid of the brackets and distribute - sign in the second bracket. 3x2 + x + 7 - 2x2 - x - 2 Step 2. Combine like terms. x2 + 5 (answer) I hope this helps.

Hello Danielle, First, bring both the equations in slope-intercept form (y = mx + b) form. Then compare slopes(m) of both equations. If the slopes are same then these lines are parallel to each other.   If, the slopes of line are negative reciprocal of each other then these...

Hello Treena, For solving this question you need to use the slope formula. m = (y2 - y1)/(x2 - x1) Given to you are the coordinates of (x1, y1) and (x2, y2) and also the slope m. x1 = 5; y1 = y; x2 = 7, y2 = -9 and m = -4 Substitute these values in the slope formula and solve...

Hello Kaz, a. For the line to be parallel the slope of both lines have be same. The equation given to you is in standard form. So, first bring the equation in slope-intercept form. 3x + 4y = 7 -3x          -3x ________________ 4y...

Hello Kayla, Graph the first inequality y > -x - 2. Since, it has > than symbol use dashed line. Now, your graph is divided in two parts. For the easiest way to find out which side of the graph you need to shade pick origin(0, 0) as your checking point. Substitute x = 0 and y = 0...

Hello Kandi, Equations given are  4x = 3y + 4  ------------------->(1) 3x = 4y + 10 ------------------->(2) As, we see from equations (1) and (2) coefficients of x or y are not same. So, to make the coefficients of x same we multiply equation (1) by 3 and...

You need to use the distributive property a(b + c) = ab + ac and vice versa ab + ac = a(b + c) Let's do the first expression 7r + 8r + 2  As you can see in first two terms r is common so take out common r(7 + 8) + 2 The other way of doing...

Hello Robyn, Two equations given are  2x - 6y = -10 -------------->equation 1 4x = 10 + 6y -------------->equation 2 We'll solve this problem using the elimination method. Solve equation 2 4x = 10 + 6y (given) -6y        -6y  (subtract...

Hello, 72 = x% * 480 72 = (x/100) * 480 Solve for x you'll get the answer. If you need further help, you can ask. Myself or any other tutor will be glad to help you.

Hello Jessica, Use FOIL method to multiply (m2 - 5)(2m2 + 3) m2(2m2 + 3) - 5(2m2 + 3) Now, distribute, combine like terms and solve you'll get your answers. I hope it helps you. If you need further assistance you can ask.

Hello Henriettas, Solve for y from first equation 4x - y = 7------------------->(first equation) -4x        -4x                       ...

Hello Connor, The constant term of this polynomial is 10, with factors 1, 2, 5, and 10. The leading coefficient is 2, with factors 1 and 2. Then the Rational roots yields the following possible solutions: ±(factors of 10)/(factors of 2) = ±(1, 2, 5, 10)/(1,2) = ±1/1, ±1/2, ±2/1, ±5/1, ±5/2, ±10/1 = ±1, ±1/2, ±2, ±5, ±5/2, ±10...

The slope intercept form for equations will be y = (2/3)x - 5/3 -----------------(1) y = (-3/2)x + 7/2 ----------------(2) As, you can see that slopes in both the equation are reciprocal and negative. That's why the lines are perpendicular to each other. Hope this helps you....

Let's start with first equation We need to bring both equations in the form y = mx + b 2x + 3y = 7            (original equation) -2x          -2x          ...

We can determine if two straight lines are either parallel or they are perpendicular by checking their slopes. y1 = m1x + b1  (equation for line 1) y2 = m2x + b2 (equation for line 2) For two lines to be parallel their slopes have to be same. That is, m1 = m2   If,...

Hello Jen, Use the point-slope formula y - y1 = m(x - x1) Here, x1 = 1 , y1 = 2 and m = 1/2 So, after substituting you'll get y - 2 = (1/2) (x - 1) y - 2 = (1/2)x - (1/2)       (distribute 1/2) Add 2 on both sides of the equation y -...